A Methods engineering study on Union Square Enterprises - Garrido, Kristina Q.; Goroy, Mark Anthony S.; Odevilas, Ver Anthony S.; Rodaje, Lea Marie T. (Diliman, Quezon City College of Engineering, 2006)
Union Square Enterprise is a furniture manufacturing company that has lately pursued for reconstruction and formalization of its production line. With this in mind, the company employed a Methods Engineering Study in order to determine the factors that contribute to its non-optimal operations and establish methods, standards, and work designs that could help reduce the effects of these factors. The conduct of the study extracted the root causes of the number of problems besetting the company. Poor documentation was detected as the single most influential root cause that results in other problems. Delayed arrival of production supplies and defective raw materials were noted to contribute also to a decrease in production rate. And material damage completes the list of the four factors that has the most impact on production under run. The study yielded some recommendations that could help the company improve its productivity. Installing a computerized database of the company's inventory and sales and making use of an inventory system to regularly check on available supplies were recommended. And changing suppliers of raw materials and setting up of additional doors on critical locations were deemed beneficial for the company to undertake.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Union Square Enterprises; Furniture industry and trade; Systems analysis